Optimal time-consistent taxation with default - Anastasios G. Karantounias (Federal Reserve Bank of Atlanta, 2017)
We study optimal time-consistent distortionary taxation when the repayment of government debt is not enforceable. The government taxes labor income or issues noncontingent debt in order to finance an exogenous stream of stochastic government expenditures. The government can repudiate its debt subject to some default costs, thereby introducing some state-contingency to debt. We are motivated by the fact that domestic sovereign default is an empirically relevant phenomenon, as Reinhart and Rogoff (2011) demonstrated. Optimal policy is characterized by two opposing incentives: an incentive to postpone taxes by issuing more debt for the future and an incentive to tax more currently in order to avoid punishing default premia. A generalized Euler equation (GEE) captures these two effects and determines the optimal back-loading or front-loading of tax distortions.
Keywords: D52; E43; E62; H21; H63; 330; labor tax; sovereign default; Markov-perfect equilibrium; time-consistency; generalized Euler equation; long-term debt